Patterning of perovskite–polymer films by wrinkling instabilities. Issue 8 (31st January 2017) - Nasti, G.; Sanchez, S.; Gunkel, I.; Balog, S.; Roose, B.; Wilts, B. D.; Teuscher, J.; Gentile, G.; Cerruti, P.; Ambrogi, V.; Carfagna, C.; Steiner, U.; et al.
Abstract : Organic–inorganic perovskites are semiconductors used for applications in optoelectronics and photovoltaics. Abstract : Organic–inorganic perovskites are semiconductors used for applications in optoelectronics and photovoltaics. Micron and submicron perovskite patterns have been explored in semitransparent photovoltaic and lasing applications. In this work, we show that a polymeric medium can be used to create a patterned perovskite, by using a novel and inexpensive approach.